National AI Security Strategies: Impacts on Universities - Glass, Chris; Kaya-Kaşıkcı, Sevgi; Chacon Camero, Eglis; Minaeva, Ekaterina (International Higher Education, 2025)
<h3 id="national-artificial-intelligence-ai-strategies-increasingly-shape-university-research-priorities-creating-complex-tensions-around-academic-openness-and-institutional-autonomy-this-analysis-examines-how-universities-navigate-competing-demands-between-international-collaboration-and-national-security-requirements-in-ai-research-and-development-it-explores-institutional-responses-as-universities-adapt-to-heightened-scrutiny-while-striving-to-maintain-their-core-academic-mission-and-international-engagement-amid-geopolitical-tensions-in-a-multipolar-world" data-pm-slice="1 1 []">National artificial intelligence (AI) strategies increasingly shape university research priorities, creating complex tensions around academic openness and institutional autonomy. This analysis examines how universities navigate competing demands between international collaboration and national security requirements in AI research and development. It explores institutional responses as universities adapt to heightened scrutiny while striving to maintain their core academic mission and international engagement amid geopolitical tensions in a multipolar world.